Rare and Combined Hepatic Artery Variants as Seen in Cadaveric and Postmortem Investigations: Anatomical Implications in Surgical Practice - Ande, Thanuja; Makani, Thanuja; Nannam, Kavya; Velichety, Subhadra; Kumar, Jyothi (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Vascular variations are an unexpected finding during cadaveric dissections, postmortems, and surgical and diagnostic angiographic procedures. Usually, such abnormalities are asymptomatic, but the existence of hepatic vasculature anomalies might cause accidental injuries to the vasculature while performing surgical procedures.Aim: This study aimed to dissect human cadavers and postmortem specimens and to examine the variations of the hepatic artery system.Materials and Method: This study was conducted on 50 specimens, with 22 conducted in the dissection hall cadavers, while 28 were collected from the postmortem among the South Indian population irrespective of age and sex and investigated for variant hepatic arteries. The data were collected between January 2014 and December 2015.Results: The results of this study demonstrated that the common hepatic artery (CHA) originated directly from the aorta in 2%, and it was trifurcated into the right hepatic artery (RHA), left hepatic artery (LHA), and gastroduodenal artery (GDA) in 8%. It continued only as the LHA in 16% and only as RHA in 4%. The RHA arises from CHA in 8%, from the superior mesenteric artery (SMA) in 10%, from GDA in 4%, and from replaced CHA in 2%. The GDA accounted for 4% of the accessory RHA's origin, while the proper hepatic artery (PHA) accounted for 2%. The LHA from the CHA in 8% replaced the origin from the left gastric artery (LGA) in 4% and replaced CHA in 2%. The middle hepatic artery was noticed in 62% of the specimens.Conclusion: Surgeons and radiologists participating in angiographic procedures must have up-to-date knowledge of hepatic artery normal variant abnormalities.
Keywords: Angiography; anomalies; hepatic artery; surgery; liver